A Simple and Efficient Approach to Elucidate Genomic Contribution of Transcripts to a Target Gene in Polyploids: The Case of Hexaploid Wheat (Triticum aestivum L.) - Chitnis, Vijaya R.; Nguyen, Tran-Nguyen; Ayele, Belay T. (Frontiers in Plant Science, 2016)
Common wheat (Triticum aestivum L.) is one of the most economically important crops in the world, however, gene functional studies in this crop have been lagging mainly due to the complexity of its polyploid genome, which is derived through two rounds of intergeneric hybridization events that led to the presence of six copies for each gene. Elucidating the transcript contribution of each genome to the total expression of a target gene in polyploids such as hexaploid wheat has a paramount significance for direct discovery of genes and the associated molecular mechanisms controlling traits of agronomic importance. A polymerase chain reaction approach that involved primers amplifying DNA fragments unique to each homeologue of a target gene and quantitation of the intensity of the resulting fragment bands were able to successfully determine the genomic transcript contributions as a percentage of target gene’s total expression in hexaploid wheat. Our results showed that the genomic contributions of transcripts vary with genotype and tissue. The approach described in this study is an effective and economical approach to elucidate the genomic transcript contribution to the total expression of individual target genes in hexaploid wheat. Such a knowledge is critical for the identification and functional characterization of novel genes regulating agronomic traits of economic importance. The method can also be applied to elucidate the transcript contribution of each genome toward the total expression of target genes in other economically important polypoid crop species.